Testing rational expectations hypothesis in the manufacturing sector in Malaysia - Puah, Chin Hong; Wong, Shirly Siew-Ling; Liew, Venus Khim-Sen (Taylor & Francis, 2013)
The application of rational expectations hypothesis (REH) in macroeconomic research has marked a revolution in economic thinking, and the magnitude of its impact on the world of economics is undeniably significant. However, the extent to which REH applies in real-world settings is ambiguous even though the concept of REH is well established in economics literature because empirical evidence from previous studies is clearly mixed. This study used survey data on gross revenue and capital expenditures to examine the validity of REH in Malaysian manufacturing business expectations. Empirical results indicated that the manufacturers’ expectations are being irrationally constructed in terms of gross revenue predictions but comply with REH properties in Muth's sense in the case of capital expenditures forecasts. Therefore, manufacturing firms in Malaysia are encouraged to incorporate more relevant information into their gross revenue predictions to provide more accurate and realistic forecasting.